Integrasi Prinsip Ekonomi Islam dalam Platform Crowdfunding Syariah: (Studi Kasus pada Pembiayaan UMKM di Indonesia) - Zohya Azzura; Eka Christina Waruwu; Ahmad Wahyudi Zein (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
Technology-based financial innovation has led to the emergence of crowdfunding platforms, which are now expanding into the realm of Islamic finance. This study aims to examine how the principles of Islamic economics are integrated into Sharia-compliant crowdfunding practices, particularly in financing Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The research employs a qualitative descriptive approach through literature review and case studies of several prominent Sharia crowdfunding platforms in Indonesia. The findings show that Sharia crowdfunding not only adheres to Islamic principles such as the prohibition of riba (usury) and gharar (uncertainty), but also applies concepts of justice, transparency, and partnership within contract structures. However, challenges related to Sharia financial literacy, regulation, and public trust remain significant obstacles. This study recommends enhancing Sharia financial literacy and strengthening regulations to support a sustainable Sharia crowdfunding ecosystem.